Profiling Tourists for Balanced Utilization of Tourism-Based Resources in Kenya - Pius Odunga; Henk Folmer (Fondazione Eni Enrico Mattei (FEEM), 2004)
Kenya is predominantly a nature-based tourism destination with wildlife (concentrated in the southern part of the country) and beaches (along the Indian Ocean) accounting for over 85% of the international tourists visiting the country. Other attractions are based on the physical landscape of the country and the culture of the people. Unfortunately, the full potential of culture-based attractions has not been exploited. The over-concentration of tourism activities in wildlife protected areas and on the coastal zone has had inherent problems that include severe environmental degradation. The less visited attractions stand the risk of neglect and could be eroded from the nation's heritage with time. There is need to diversify tourism activities and spread them to other parts of the country by putting more emphasis on non-traditional ones such as cultural excursions. This research profiles tourists based on their preferences as assessed from the number of days they spend at different attraction sites. By associating the characteristics of tourists with various attractions, consumer preference profiles were established. Length of stay, presence of children, travel party size and gender are some of the significant factors that determined the profiles. Profiles can be used in encouraging proportionately more tourists with greater affinity for non-traditional attractions. Besides gender, other factors such as socio-economic status and whether one is travelling as a couple or not, turned out to be significant variables in influencing the resulting expenditure levels.
Keywords: 330; Tourist profiles; Attractions; Culture; Expenditure; LISREL; Kenya